'Derivative/Hedging' Deals—Volume Ii : By Citibank, Standard Chartered Bank, Deutsche Bank, with Sri Lanka Government'S Petroleum Corporation—Dubious & Illegal? /: By Citibank, Standard Chartered Bank, Deutsche Bank, with Sri Lanka Government'S Petroleum Corporation—Dubious & Illegal?. (2017) - Ameresekere, Nihal Sri
No abstract available